Why Do Workers Make Job Referrals? Experimental Evidence from Ethiopia - Marc J. Witte (Institute of Labor Economics (IZA), 2025)
What motivates workers' referral decisions? Combining a field experiment in a firm and urban social network data, I first show that workers primarily refer those who previously referred them. This reciprocity leads to significant on-the-job productivity losses and excludes less connected individuals. Incentivized referrals reduce reciprocity and make workers screen more productive colleagues. Second, peripheral workers use referrals strategically to establish new and reciprocated links which persist after 18 months. These results are consistent with a network-based referral model where individuals trade off pecuniary and social incentives. The findings suggest that referrals through social networks can reinforce labor market inequalities.
Keywords: 330; job referrals; social networks; field experiment